Sensitivity and specificity of polymerase chain reaction in Giemsa-stained slides for diagnosis of visceral leishmaniasis in children - Brustoloni, Yvone Maia (2007)
The aim of this study was to evaluate the sensitivity and specificity of polymerase chain reaction (PCR) in the detection of Leishmania DNA in archived Giemsa-stained bone marrow slides for diagnosis of visceral leishmaniasis (VL), and to compare PCR with conventional diagnostic techniques, like direct microscopy and parasite culture. Specimens of archived Giemsa-stained bone marrow slides from 91 patients with VL and from 79 controls with other diseases or conditions were studied. PCR showed the highest sensitivity (92.3%) and had good specificity (97.5%). Direct examination detected 79.1% and culture 59% of positive samples. In addition, PCR was able to detect VL in 16 of 19 patients (84.2%) with negative microscopy. PCR in Giemsa-stained bone marrow slides is a suitable tool for confirming diagnosis in patients with VL and may be useful in the diagnosis of difficult cases. Slide smears are easily stored, do not require special storage conditions such as low temperatures, and can be easily mailed to centers where PCR is available, making it an excellent option for diagnosis in the field.